Terrorism and the Performance of Journalists in Balochistan - Nauman Khan; Riffat Alam; Muhammad Junaid Ghauri (Journal of Business and Social Review in Emerging Economies, 2022)
Purpose: Freedom of speech and freedom of the press is generally attributed to an independent society where the basic rights of citizens are ensured. Balochistan, the western and resources rich province of Pakistan with its huge geopolitical importance has been under a strong wave of terrorism for the last two decades. This menace of terrorism has severely affected citizens of the province including media workers.